Reflux of Anterior Spinal Artery Predicts Recurrent Posterior Circulation Stroke in Bilateral Vertebral Artery Disease. Issue 11 (November 2015) - Fukuda, Hitoshi; Hayashi, Kosuke; Handa, Akira; Kurosaki, Yoshitaka; Lo, Benjamin; Yamagata, Sen
Abstract : Backgrounds and Purpose—: Predictive value of reflux of anterior spinal artery for recurrent posterior circulation ischemia in bilateral vertebral arteries steno-occlusive disease was evaluated. Methods—: We retrospectively reviewed 55 patients with symptomatic posterior circulation stroke caused by bilateral stenotic (>70%) lesions of the vertebral artery. We investigated any correlation of clinical and angiographic characteristics including collateral flow patterns, with recurrent stroke. Risk factors for poor 3-month functional outcome were also evaluated. Results—: Recurrent posterior circulation stroke was observed in 15 (27.3%) patients. Multivariable analysis using Cox proportional hazards model showed anterior spinal artery reflux as a significant risk factor for stroke recurrence (adjusted hazard ratio, 19.3 [95% confidence interval, 5.35–69.9]; P <0.001). Anterior spinal artery reflux was also correlated with poor functional outcome (modified Rankin Scale score, 3–6; adjusted odds ratio, 7.41 [95% confidence interval, 1.24–44.4]; P =0.028). Conclusions—: In patients with symptomatic bilateral vertebral artery occlusive disease, anterior spinal artery reflux predicted recurrent posterior circulation stroke and poor functional outcome.